Thermally conductive composition and method for producing a thermally conductive composition

JP2026165113APending Publication Date: 2026-10-13MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026053295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-27
Filing Date
2026-03-27
Publication Date
2026-10-13

Smart Images

  • Figure 2026165113000001
    Figure 2026165113000001
Patent Text Reader

Abstract

The present invention provides a thermally conductive composition having excellent coatability and a method for producing the same. [Solution] A thermally conductive composition is employed, characterized by comprising a liquid metal containing gallium and one or more of indium and tin, and containing 0.2 to 0.5 wt% oxygen. Furthermore, a method for producing the thermally conductive composition is employed, characterized by stirring only the liquid metal containing gallium and one or more of indium and tin in the presence of oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a thermally conductive composition and a method for producing a thermally conductive composition. [Background technology]

[0002] In recent years, as various electronic devices have become more high-performance and integrated, there has been a growing demand for structures that enhance heat dissipation, allowing the heat generated by the operation of components (heat-generating elements) to be dissipated to the outside using heat dissipation materials.

[0003] To reduce the thermal resistance between a heat-generating element and a heat-dissipating component, a heat transfer material is sometimes placed between the heat-generating element and the heat-dissipating component. By using a heat transfer material, for example, the heat generated by the heat-generating element can be efficiently dissipated to a heat-dissipating component such as a metal casing or heat sink. By placing such a heat transfer material between the heat-generating element and the heat-dissipating component, the thermal resistance between the heat-generating element and the heat-dissipating component can be reduced.

[0004] For example, Patent Documents 1 and 2 propose thermally conductive compositions using liquid metals. Patent Document 1 discloses a paste containing 50 mass% tungsten as a filler in 50 mass% Ga-In-Sn ternary eutectic alloy (liquid metal).

[0005] Patent Document 2 discloses a heat dissipation grease composition comprising an alloy as a base material containing gallium (Ga), indium (In), and / or tin (Sn), having a melting point of 16°C or lower under normal pressure, and a fine powder filler consisting of a metal (e.g., silver, copper, etc.) included in 2 to 40 mass%, with a consistency in the range of 200 to 400. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Special Publication No. 7-029213 [Patent Document 2] Patent No. 5542280 [Overview of the project] [Problems that the invention aims to solve]

[0007] Liquid metals are liquid at room temperature, but their high surface tension and low adhesion to heat-generating elements and heat-dissipating components make them difficult to apply as heat transfer materials. Adding fillers to liquid metals does not change the properties of the liquid metal itself, so there is room for improvement in terms of application properties.

[0008] The present invention has been made in view of the circumstances described above, and aims to provide a thermally conductive composition having excellent coatability and a method for producing the same. [Means for solving the problem]

[0009] In order to solve the above problems, the inventors conducted diligent research and found that by oxidizing the liquid metal and incorporating a desired amount of oxygen, the surface tension of the liquid metal can be reduced, thereby improving its coatability.

[0010] This invention is based on the above findings. [1] A liquid metal comprising gallium and one or more of indium and tin, A thermally conductive composition characterized by containing 0.20 to 0.50 wt% oxygen. [2] Viscosity of 1 × 10 at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s) 4 ~1 × 10 6 The thermally conductive composition according to [1], characterized in that it is Pa·s. [3] The thermal conductive composition according to [1] or [2], characterized in that the tip is mirror-finished and the adhesive strength to the surface of a Φ5 mm cylindrical PTFE probe is 1.0 to 50.0 gf. [4] A thermally conductive composition according to any one of [1] to [3], characterized in that the void ratio is 20 to 60%. [5] A method for producing a thermally conductive composition according to any one of [1] to [4], characterized by stirring only a liquid metal containing gallium and one or more of indium and tin in the presence of oxygen. [Effects of the Invention]

[0011] According to the present invention, it is possible to provide a thermally conductive composition having excellent coatability and a method for producing the same. Furthermore, the viscosity can be adjusted by controlling the degree of oxidation of the thermally conductive composition, making it easier to handle as a paste. Furthermore, the tackiness can be adjusted by controlling the degree of oxidation, improving the retention of components (heating elements, etc.) and preventing the components (heating elements, etc.) from shifting during the manufacturing process. [Modes for carrying out the invention]

[0012] A thermally conductive composition and a method for manufacturing the same, which are embodiments of one invention, will be described. First, the thermally conductive composition according to this embodiment will be described.

[0013] The thermally conductive composition according to this embodiment is, for example, placed as a heat transfer material between a component (heat-generating element) and a heat-dissipating member, and transfers the heat generated from the heat-generating element to the heat-dissipating member. Furthermore, in this specification, a thermally conductive composition refers to a composition having a thermal conductivity of 10 W / m·K or higher. The thermally conductive composition according to this embodiment consists of a liquid metal comprising gallium and one or more of indium and tin, and contains 0.20 to 0.50 wt% oxygen.

[0014] The liquid metal constituting the thermally conductive composition is liquid at atmospheric pressure and 25°C, and contains gallium (Ga) and one or more of indium (In) and tin (Sn). The composition of the liquid metal is preferably Ga: 60.0 to 80.0 mass%, In: 0.0 to 25.0 mass%, Sn: 0.0 to 20.0 mass%, and the total content of In and Sn is 20.0 to 40.0 mass%. It is not necessary to contain both In and Sn, and the content of either one of them may be 20.0 to 40.0 mass%.

[0015] The liquid metal may contain other alloying elements. As the alloying elements, for example, one or more of zinc (Zn) and bismuth (Bi) may be contained. These alloying elements may be contained at Zn: 0.0 to 5.0 mass% and Bi: 0.0 to 5.0 mass%, respectively. Furthermore, when impurity elements other than Zn and Bi are contained, the total content of the impurity elements is preferably 5.0 mass% or less.

[0016] The composition of the liquid metal is measured by ICP optical emission spectrometry in accordance with JIS K 0116:2014.

[0017] The liquid metal containing the above-described elements has a high surface tension, forms droplets, and does not become a paste. For this reason, it is not possible to ensure coatability with members such as heating elements and heat dissipation members. Therefore, in the present embodiment, a desired amount of oxygen is contained in the liquid metal to increase the viscosity of the liquid metal and improve the coatability.

[0018] The thermally conductive composition according to the present embodiment contains 0.20 to 0.50 wt% of oxygen. If the oxygen content (mass of oxygen / mass of the thermally conductive composition) is less than 0.20 wt%, the viscosity will be insufficient and the composition will not be in a paste form, making it difficult to handle as a thermally conductive composition. Therefore, the oxygen content is set to 0.20 wt% or more. The oxygen content is preferably 0.25 wt% or more, and more preferably 0.30 wt% or more. On the other hand, if the oxygen content exceeds 0.50 wt%, the viscosity becomes excessively high to form a solid state, making it difficult to handle as a thermally conductive composition. Furthermore, the tackiness decreases. Therefore, the oxygen content is set to 0.50 wt% or less. From the viewpoint of further enhancing tackiness, the oxygen content is preferably 0.45 wt% or less, and more preferably 0.40 wt% or less.

[0019] The thermally conductive composition according to the present embodiment preferably has a viscosity of 1×10 at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s) 4 ~1×10 6 Pa·s. By having this viscosity, the thermally conductive composition is in a "paste state", and can be judged to have a viscosity that allows easy handling as a thermally conductive composition.

[0020] Note that in the present embodiment, the "paste state" refers to, as described above, a viscosity of 1×10 at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s) 4 ~1×10 6 Pa·s (1×10 4 Pa·s or more, and 1×10 6 Pa·s or less). The "solid state" refers to a state where the viscosity exceeds 1×10 6 Pa·s, and the "liquid state" refers to a state where the viscosity is less than 1×10 4 Pa·s. For the viscosity measurement, a parallel plate rheometer (Discovery HR 20, manufactured by TA Instruments in the present embodiment) is used.

[0021] The oxygen content of the thermally conductive composition is measured by the following method. The oxygen amount is measured based on JIS Z 2613:2020 using the inert gas fusion-infrared absorption method.

[0022] The thermal conductive composition according to this embodiment preferably has a mirror-finished tip and an adhesive strength of 1 to 50 gf to the surface of a Φ5 mm cylindrical PTFE probe. If the tip is mirror-finished and the adhesive strength to the surface of a Φ5 mm cylindrical PTFE probe is 1 to 50 gf, it can be determined that it has excellent tackiness. Adhesion strength is measured using a tacking tester (TAC1000, manufactured by Resca Co., Ltd.) in accordance with JIS Z 3284-3:2024. For the measurement, a Φ5 mm PTFE probe is used, and the probe is lowered onto the sample at a speed of 2 mm / s, after which pressure is applied until a pressure of 0.03 MPa is reached. After 0.1 seconds, the probe is withdrawn from the sample (sample thickness 2 mm) at a speed of 10 mm / s.

[0023] The thermal conductive composition according to this embodiment preferably has a void ratio of 20 to 60%. If the void ratio is 20% or more, the viscosity of the thermal conductive composition can be preferably adjusted. A void ratio of 40% or more is more preferable. Furthermore, if the void ratio is 60% or less, the thermal conductivity and adhesive strength of the thermal conductive composition can be preferably adjusted.

[0024] The void ratio is measured by the following method. First, a thermally conductive composition is filled between two glass plates separated by a 0.5 mm gap. Two glass plates filled with a thermally conductive composition are used to observe the composition from one side using X-ray CT, and a transmission image of the thermally conductive composition is captured. The obtained transmission image is binarized using image processing software (ImageJ), and the area of ​​the void-free portion and the area of ​​the void portion of the thermally conductive composition are determined from the binarized image. The contrast threshold for binarization is set to a value that separates the luminance of the voids and the matrix phase (liquid metal phase) by checking the luminance value distribution (e.g., in the range of 0 to 255) of the grayscale image of the transmission image. The void fraction is calculated from the obtained area of ​​the void-free portion and the area of ​​the void portion of the thermally conductive composition using the following formula. The void fraction is measured in three 10 mm × 10 mm areas for each sample. Void fraction (%) = {Area of ​​voided portion / (Area of ​​void-free portion of thermally conductive composition + Area of ​​voided portion)} × 100

[0025] Next, a method for producing the above-mentioned thermally conductive composition will be described. In the method for producing the thermally conductive composition according to this embodiment, only a liquid metal containing gallium and one or more of indium and tin is stirred in the presence of oxygen.

[0026] Normally, liquid metal is mixed with fillers, but in this embodiment, only the liquid metal is stirred in the presence of oxygen without adding any fillers. By stirring only the liquid metal in the presence of oxygen, not only the surface of the liquid metal but the entire liquid metal can be uniformly oxidized. As a result, a thermally conductive composition containing the desired amount of oxygen can be obtained.

[0027] The method of stirring the liquid metal is not particularly limited; it may be stirred manually in the presence of oxygen, or a rotary mixer or the like may be used. The presence of oxygen is, for example, air. For example, when stirring at a stirring speed of 2000 rpm using a rotary-rotating mixer, it is preferable to stir for 5 to 60 minutes, and more preferably 10 to 40 minutes, in order to sufficiently oxidize the liquid metal and obtain the desired void ratio. The stirring speed and stirring time should be appropriately adjusted according to the stirring method so that the desired oxygen content and void ratio are obtained in the liquid metal.

[0028] Liquid metal before stirring is obtained by heating the raw materials. First, the gallium (Ga), indium (In), and / or tin (Sn) raw materials that constitute the liquid metal are prepared and weighed out in predetermined proportions. By mixing these raw materials while heated, a liquid metal of a predetermined composition is formed. The formed liquid metal becomes liquid at atmospheric pressure and 25°C. Furthermore, it is preferable to adjust the heating temperature and holding time depending on the composition and amount of the liquid metal. The heating temperature should preferably be between 80 and 200°C, and the holding time at this temperature should preferably be 5 minutes or more.

[0029] The thermally conductive composition according to this embodiment, as described above, consists of a liquid metal comprising gallium and one or more of indium and tin, and contains 0.20 to 0.50 wt% oxygen, thereby exhibiting excellent coating properties.

[0030] In the thermally conductive composition according to this embodiment, the viscosity at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s) is 1 × 10⁻¹⁶. 4 ~1 × 10 6 If it is Pa·s, it can be determined to be in paste form and can be easily handled as a thermally conductive composition.

[0031] In the thermal conductive composition according to this embodiment, if the tip is mirror-finished and the adhesive strength to the surface of a Φ5 mm cylindrical PTFE probe is 1 to 50 gf, the tackiness can be further increased, and the holding ability of components (heating elements, etc.) can be improved.

[0032] In the thermally conductive composition according to this embodiment, when the void ratio is 20 to 60%, it is possible to have viscosity and adhesive strength within the above range while maintaining high thermal conductivity.

[0033] According to the method for producing the thermally conductive composition of this embodiment, the above-mentioned thermally conductive composition containing a desired amount of oxygen can be obtained by stirring only a liquid metal containing gallium and one or more of indium and tin in the presence of oxygen.

[0034] Although embodiments of the present invention, namely a thermally conductive composition and a method for producing the thermally conductive composition, have been described above, the present invention is not limited thereto and can be modified as appropriate without departing from the technical spirit of the invention. [Examples]

[0035] The results of the verification experiments conducted to confirm the effects of the present invention are described below.

[0036] Powdered raw materials of Ga, In, and Sn were heated to 100°C and held for 20 minutes, then mixed to obtain a liquid metal with the following concentrations: Ga: 68.5 wt%, In: 21.5 wt%, and Sn: 10.0 wt%. Using the obtained liquid metal, a thermally conductive composition was prepared by stirring in the presence of oxygen (in air) according to the method described in Table 1. Note that stirring was not performed in No. 1.

[0037] The obtained thermally conductive compositions were evaluated for their state, oxygen content, adhesive strength, and void ratio using the method described above. The state of the thermally conductive composition was judged according to the following criteria based on viscosity at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s). Liquid: 1 x 10 4 Less than Pa·s Paste form: 1 x 10 4 ~1 × 10 6 Pa·s Solid form: 1×10 6 Pa·s super Furthermore, the void fractions listed in Table 1 are the average of the void fractions measured using the method described above.

[0038] Furthermore, the thermal conductivity and coatability of the thermally conductive composition were evaluated using the following method.

[0039] Thermal conductivity was measured using a thermal conductivity measuring device (TRM-046RHHT, manufactured by Hitachi Technology & Services, Ltd.) by the steady-state method.

[0040] The coating properties were evaluated by placing 1 g of the thermal conductive composition on a glass plate, spreading it 5 cm with a 1.5 cm wide spatula, and checking for the presence or absence of uncoated areas by visual inspection or using a microscope (VHX-970F: manufactured by Keyence Corporation). If there were no uncoated areas with a diameter of 5 mm or more, it was marked as "Good" indicating excellent coating properties. If there were uncoated areas with a diameter of 5 mm or more, it was marked as "Bad" indicating poor coating properties.

[0041] The results obtained are shown in Table 1. Underlined text in the table indicates that a result falls outside the scope of the present invention or exhibits undesirable characteristics.

[0042] [Table 1]

[0043] Based on the above, according to the present invention, a thermally conductive composition having excellent coatability and a method for producing the same can be obtained. [Industrial applicability]

[0044] The present invention provides a thermally conductive composition having excellent coatability and a method for producing the same.

Claims

1. It consists of a liquid metal containing gallium and one or more of indium and tin. A thermally conductive composition characterized by containing 0.20 to 0.50 wt% oxygen.

2. The viscosity at a measurement temperature of 25°C and a shear rate of 0.1 (1 / s) is 1 × 10⁻¹⁶. 4 ~1 x 10 6 The thermally conductive composition according to claim 1, characterized in that it is Pa·s.

3. The thermal conductive composition according to claim 1, characterized in that the tip is mirror-finished and the adhesive strength to the surface of a cylindrical PTFE probe with a diameter of Φ5 mm is 1 to 50 gf.

4. The thermal conductive composition according to claim 2, characterized in that the tip is mirror-finished and the adhesive strength to the surface of a Φ5 mm cylindrical PTFE probe is 1 to 50 gf.

5. A thermally conductive composition according to any one of claims 1 to 4, characterized in that the void ratio is 20 to 60%.

6. A method for producing a thermally conductive composition according to any one of claims 1 to 4, characterized by stirring only a liquid metal containing gallium and one or more of indium and tin in the presence of oxygen.

7. A method for producing a thermally conductive composition according to claim 5, characterized by stirring only a liquid metal containing gallium and one or more of indium and tin in the presence of oxygen.

Citation Information

Patent Citations

  • Production of smoked pottery having silver luster

    JP1980042280A

  • Optical recording disk

    JP1995029213A